Formação de professores: um estudo das condições objetivas na implementação do Plano Nacional de Formação de Professores para a Educação Básica – PARFOR/UFMA - Santos Neta, Aldenora Resende dos (2016)
This work, entitled "Teacher Training: a study of objective conditions in the implementation of the National Plan of Teacher Training for Basic Education - PARFOR / UFMA", aimed to analyze the objective conditions for the development of courses Training Program Teachers for Basic Education (PARFOR), in the Universidade Federal do Maranhão (UFMA). Therefore, we present reflections on the subject, object of research and academic studies on teacher training. in Brazil. In addition, we discussed the training of teachers since the 1990s, as well as content, principles and requirements in the present policies that legitimize the Teacher Training Program for Basic Education (PARFOR / UFMA). We analyze the objective conditions (socioeconomic, cultural, material and human) to develop the program from the perspective of student-teachers, teacher-trainers, the course coordinators, general coordinator of the program and local coordinators of Municipal Education. We also analyze the impact on learning of student-teachers in relation to working hours and study time, from the understanding of the subjects. The work was the theoretical philosopher Theodor W. Adorno ideas about "empowerment" and " semi-formation", as well as Brazilian studies dealing with policy and teacher training as Brzenzinki (1999, 2010), Demo (1997), Dourado (2007), Frigotto and Ciavatta (2003), Gatti, Sá Barreto, André (2011), Saviani (2006), Shigunov and Maciel (2004), Zeichner (1998), Giroux (1997) and Contreras (2002), etc. . We work with documentary data sources and individual semi-structured interviews with members linked to PARFOR UFMA such as: General coordinator of PARFOR/UFMA (1); studentteachers (16); the Course Coordinators (2); teacher-trainers (8) Members of the City Department of Education (2). In total, 29 subjects were interviewed, which are part of the Teacher Training Program for Basic Education of the UFMA, in the municipalities Humberto de Campos/MA and Coroatá/MA. The results of this study revealed limitations and gaps in the implementation of the program, especially when it comes to respect for the physical, material, human and cultural, which may have influenced the learning of student teachers enrolled in the program. Therefore, we believe it is necessary to review the role and responsibility of the University, the State Department of Education and municipal education secretariats and the Union as regards the implementation of emergency teacher-training programs for basic education, to ensure a solid formation able to awaken the subject autonomy, empowerment and resistance to the dictates of the cultural industry and erudition.